Analysis of Characteristics and Risk Factors for the Incidence of Coronary Heart Disease in Hospitals General Royal Prima for the Period January-December 2024 - Dinda Permata; Taufik Delfian; Ana Fresia (International Journal Labs, 2025)
Coronary heart disease (CHD) is still the leading cause of death globally and nationally and is closely related to various cardiometabolic and behavioral risk factors. This study aims to analyze the characteristics and risk factors related to the incidence of CHD at Royal Prima Hospital for the January-December 2024 period. The research design used an observational analytical study with a medical record-based case-control approach, involving 120 respondents (60 CHD cases and 60 non-CHD cases) who were selected by consecutive sampling. Independent variables included age, gender, hypertension, dyslipidemia, diabetes mellitus, obesity, and smoking history. Data analysis was carried out in univariate, bivariate (Chi-Square test), and multivariate (binary logistics regression). The results showed that all risk factors were significantly related to the incidence of CHD in bivariate analysis (p < 0.05). Multivariate analysis showed that age ?45 years, dyslipidemia, hypertension, diabetes mellitus, smoking history, and male sex had a significant effect on CHD, with age ?45 years as the most dominant factor, while obesity had no independent effect. These findings confirm the importance of controlling the main risk factors in the prevention of CHD in health care facilities.